A Flexible Film toward High‐Performance Lithium Storage: Designing Nanosheet‐Assembled Hollow Single‐Hole Ni–Co–Mn–O Spheres with Oxygen Vacancy Embedded in 3D Carbon Nanotube/Graphene Network. Issue 27 (22nd May 2019) - Li, Sesi; Zhao, Xuebing; Feng, Yuzhang; Yang, Liting; Shi, Xiaofeng; Xu, Pingdi; Zhang, Jie; Wang, Peng; Wang, Min; Che, Renchao
Abstract: Ternary transition metal oxides (TMOs) are highly potential electrode materials for lithium ion batteries (LIBs) due to abundant defects and synergistic effects with various metal elements in a single structure. However, low electronic/ionic conductivity and severe volume change hamper their practical application for lithium storage. Herein, nanosheet‐assembled hollow single‐hole Ni–Co–Mn oxide (NHSNCM) spheres with oxygen vacancies can be obtained through a facile hydrothermal reaction, which makes both ends of each nanosheet exposed to sufficient free space for volume variation, electrolyte for extra active surface area, and dual ion diffusion paths compared with airtight hollow structures. Furthermore, oxygen vacancies could improve ion/electronic transport and ion insertion/extraction process of NHSNCM spheres. Thus, oxygen‐vacancy‐rich NHSNCM spheres embedded into a 3D porous carbon nanotube/graphene network as the anode film ensure efficient electrolyte infiltration into both the exterior and interior of porous and open spheres for a high utilization of the active material, showing an excellent electrochemical performance for LIBs (1595 mAh g −1 over 300 cycles at 2 A g −1, 441.6 mAh g −1 over 4000 cycles at 10 A g −1 ). Besides, this straightforward synthetic method opens an efficacious avenue for the construction of various nanosheet‐assembled hollow single‐hole TMO spheres for potential applications. Abstract : Nanosheet‐assembled hollow single‐hole Ni–Co–Mn oxide spheres with oxygen vacancies in a carbon nanotube/graphene network as a flexible anode for lithium storage are fabricated by facile technology, which make both ends of the nanosheets exposed to sufficient space for volume change, and electrolyte for dual ion diffusion paths. This technology opens an avenue for the novel structural construction of transition metal oxides.